The Retro-Futurism of Cuteness - Boyle, Jen; Kao, Wan-Chuan (punctum books, 2017)
Is it possible to conceive of a Hello Kitty Middle Ages or a Tickle Me Elmo Renaissance? The Oxford English Dictionary dates the first reference to "cute" in the sense of "attractive, pretty, charming" to 1834. More recently, Sianne Ngai has offered a critical overview of the cuteness of the twentieth-century avant-garde within the context of consumer culture. But if cuteness can get under the skin, what kinds of surfaces does it best infiltrate, particularly in the framework of historical forms, events, and objects that traditionally have been read as emergences around "big" aesthetics of formal symmetries, high affects, and resemblances? The Retrofuturism of Cuteness seeks to undo the temporal strictures surrounding aesthetic and affective categories, to displace a strict focus on commodification and cuteness, and to interrogate how cuteness as a minor aesthetics can refocus our perceptions and readings of both premodern and modern media, literature, and culture. Taking seriously the retro and the futuristic temporalities of cuteness, this volume puts in conversation projects that have unearthed remnants of a "cult of cute"-positioned historically and critically in between transitions into secularization, capitalist frameworks of commodification, and the enchantment of objects-and those that have investigated the uncanny haunting of earlier aesthetics in future-oriented modes of cuteness.